The Association between Socioeconomic Characteristics and Consumption of Food Items among Brazilian Industry Workers - Vinholes, Daniele B. (2012)
Background. Dietary pattern plays a causative role in the rising of noncommunicable diseases. the SESI (Servico Social da Industria) study was designed to evaluate risk factors for noncommunicable diseases. We aimed to describe food items consumed by Brazilian workers and to assess their association with socioeconomic status. Methods. Cross-sectional study was carried out among Brazilian industrial workers, selected by multistage sampling, from 157 companies. Interviews were conducted at the work place using standardized forms. Results. 4818 workers were interviewed, aged 35.4 +/- 10.7 years, 76.5% were men. the workers had an average of 8.7 +/- 4.1 years of schooling and 25.4 +/- 4.1 kg/m(2) of BMI. Men and individuals with less than high school education were less likely to consume dairy products, fruits, and vegetables daily, even after control for confounding factors. Men consumed rice and beans daily more often than women. in comparison to workers aged 50-76 years, those under 30 years old consumed less fruits and green leafy vegetables daily. Conclusion. the food items consumed by Brazilian workers show that there are insufficient consumption according to the guidelines of healthy foods, particularly of dairy products, vegetables, and fruits.